“‘From different books we must ask different qualities’: The Essay as Public or Private Space in the Yale Review and Common Reader versions of Virginia Woolf’s ‘How Should One Read a Book?’” - Xavier LE BRUN (E-REA)
The genesis and publication history of Virginia Woolf’s “How Should One Read a Book?”, whose final version appeared in The Second Common Reader in 1932, is by now well-established. Critics, including Andrew McNeillie and Beth Rigel Daugherty, have traced its inception in a lecture given by Woolf in 1926 and documented the successive revisions undergone by the text. In the wake of such studies, this paper focuses on the differences between the Yale Review and the Common Reader versions of “How Should One Read a Book?” to suggest that the change in medium – periodical vs. book-form essay – alters Woolf’s relationship to the subject she is writing about: reading books. Whereas in The Common Reader, Woolf is writing from within the field she explores (books and their various “classes”), The Yale Review essay approaches the same question from the perspective of the journal article. As I argue, a number of the differences between the two versions of the essay – including the reading strategy devised by Woolf – are accountable to this change of perspective.